Development of Powder Metallurgy (PM) compacted Cu-TaC electrode for EDM - Mohammed , Baba Ndaliman; Khan, Ahsan Ali (IIUM, 2011)

(untitled)
The main aim of this paper is to investigate the properties of TaC-Cu electrodes produced by Powder Metallurgy (PM) method. The design of Experiment (DOE) method was used to plan the investigation. Two different compositions of the powders (Cu-TaC with 30 and 55 % wt TaC) were used. The major properties which determine suitability of electrodes for Electro Discharge Machining (EDM) are electrical conductivity,thermal conductivity and to some extent density. These properties were measured for the green compacted electrodes,analyzed and compared with their sintered counterparts. This is the initial stage to determine the suitability or otherwise of the compacted electrodes. The results showed that the compacted electrodes in green form can be suitable for EDM, since the electrical conductivities are very high (94.96 – 189.92-1m-1). The thermal conductivity is good (29.70 – 33.20W/ m K). The density ranges between 6.13 and 9.80 g/cm3. The sintered electrodes were found to be unsuitable at the specified conditions, because they became non-conductive electrically after sintering. Current efforts are geared towards improving these properties for the sintered ones and also determining their optimum levels.